-6-4x=6(1-7x)+4x

Simple and best practice solution for -6-4x=6(1-7x)+4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6-4x=6(1-7x)+4x equation:


Simplifying
-6 + -4x = 6(1 + -7x) + 4x
-6 + -4x = (1 * 6 + -7x * 6) + 4x
-6 + -4x = (6 + -42x) + 4x

Combine like terms: -42x + 4x = -38x
-6 + -4x = 6 + -38x

Solving
-6 + -4x = 6 + -38x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '38x' to each side of the equation.
-6 + -4x + 38x = 6 + -38x + 38x

Combine like terms: -4x + 38x = 34x
-6 + 34x = 6 + -38x + 38x

Combine like terms: -38x + 38x = 0
-6 + 34x = 6 + 0
-6 + 34x = 6

Add '6' to each side of the equation.
-6 + 6 + 34x = 6 + 6

Combine like terms: -6 + 6 = 0
0 + 34x = 6 + 6
34x = 6 + 6

Combine like terms: 6 + 6 = 12
34x = 12

Divide each side by '34'.
x = 0.3529411765

Simplifying
x = 0.3529411765

See similar equations:

| x^2-4x+4+56=x^2 | | 35-3v=4v | | 43=4x+3 | | 6(6x-1)+4x=5x+50 | | q+7=8q+14 | | a(4a-15)=25 | | .45x+.05(14-x)=.10(71) | | 49x^2+28x+2=0 | | 2+-2=20 | | 10a=6a+36 | | x^4=x^4-8x^3+24x^2-32x+56+6 | | 4(-5)+(-5)+8=-32-3(-5) | | x^4=x^4-8x^3+24x^2-32x+56 | | -28a+21=-35 | | 15954a+1690b+1043c=127830000 | | a+b+c=25900 | | 36-9r=r*r | | 2n-1=8191 | | =6.5-0.83t | | 64=.5(x^2+8x) | | 7-6x=7+5x+5x | | =6.5t-0.83t^2 | | f(x)=5x^3+8x^2-4x^4 | | 5x-1/3=5-3 | | 0=(6.5t-0.83t^2) | | 3(y+5)-2(2y-5)=25 | | 3^-7x^5y^3/3^-4x^-8y^6 | | 17-2x=2(3x+5)+x | | y=(x+3)(x+3)(x-5-3i)(x-5+3i) | | 13-2b=b+4 | | 13x-2=7x+12 | | 5=(-z)-3 |

Equations solver categories